Multinational Enterprises’ Knowledge Transfer Received Dimensions and Subsidiary Innovation Performance: The Impact of Human Resource Management Practices and Training and Development Types - Xie, Yu; Boadu, Francis; Chen, Zhen; Ofori, Adwoa Serwaa (Frontiers in Psychology, 2022)
In this paper, we adopt the resource-based view, ability-motivation-opportunity, and social learning theories as the theoretical framework to empirically investigate the relationship among knowledge transfer received dimensions (i.e., tacit and explicit), human resource management practices, training and development types (i.e., on-the-job training and development and off-the-job training and development) and subsidiary innovation performance. Using a survey dataset from 314 subsidiaries of foreign MNEs located in China, we find that: (1) knowledge transfer received dimensions contribute to subsidiary innovation performance; (2) human resource management practices can positively moderate knowledge transfer received dimensions and subsidiary innovation performance; (3) the positive effect of human resource management practices on the knowledge transfer received dimensions- subsidiary innovation performance link increases when on-the-job and off-the-job training and development is high. The study also provides insight into how knowledge transfer received dimensions, human resource management practices, and training and development types matter importantly to the subsidiary's innovation performance.